1997
DOI: 10.1108/09600039710162259
|View full text |Cite
|
Sign up to set email alerts
|

Information technology influences on world class logistics capability

Abstract: Information technology has been among the foremost topics within the logistics literature of recent years. However, there has been little empirical evidence relating logistics information system (LIS) capabilities to logistics competence. Seeks to close this gap in the research, identify particular LIS capabilities that contribute most to logistics competence, and develop an understanding of the relationship between LIS development strategy and logistics competence. A review of the LIS literature identifies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(176 citation statements)
references
References 15 publications
5
166
1
4
Order By: Relevance
“…These arguments collectively suggest the development of our first research hypothesis: H 1 IT adoption has a positive impact on 3PLs' performance. Closs et al (1996) and Piplani et al (2004) suggest that the adoption of information technologies by 3PLs enable them to acquire specific knowledge and skills that are core to their business. Lai (2004) suggests that the skills acquired via technological innovation are employed by 3PLs to offer a set of services to their clients.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…These arguments collectively suggest the development of our first research hypothesis: H 1 IT adoption has a positive impact on 3PLs' performance. Closs et al (1996) and Piplani et al (2004) suggest that the adoption of information technologies by 3PLs enable them to acquire specific knowledge and skills that are core to their business. Lai (2004) suggests that the skills acquired via technological innovation are employed by 3PLs to offer a set of services to their clients.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Under those circumstances, the information produced in logistics processes becomes a vital element for an adequate management of inventories and, in this way, in an essential complement of materials flow (Closs et al, 1997). Consequently, managers of enterprises will have a better position to make better decisions by having factual and timely information produced by means of the flexibility of logistics systems which can create better result than those enterprises that make decisions by dividing the two func tions (Lee & Whang, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2002) conducted a wider survey and identified the following ranking of deficient variables: reputation, conciseness, accessibility, and ease of operation. Closs et al (1997) ranked the capability of information systems, where orders and forecasts rank equal -from format, through availability and timelines, to accuracy (Table 1). In general, accuracy and timeliness have high ranks in three of four rating systems.…”
Section: Information Qualitymentioning
confidence: 99%